Tinjauan Hukum Islam terhadap Uang Mahar Perkawinan (Studi Kasus Desa Janjilobi Kecamatan Barumun Kabupaten Padang Lawas) - Salamat Martua Nasution; Ismail Nasution; Nurhakima Akhirani Nasution (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
This study aims to: 1) determine the concept of marriage dowry in Janjilobi Village, Barumun District, Padang Lawas Regency. 2) determine whether the dowry has been implemented in Janjilobi Village, Barumun District, Padang Lawas Regency according to Islamic law. This research method is field research, with primary data sources consisting of answers to interviews with respondents and secondary data, namely books, journals, and other supporting documents. Data collection methods include observation, interviews, and documentation. Data analysis methods, data reduction methods, data presentation, and conclusion drawing are used. Data validity checking techniques include data credibility testing, dependability testing, transferability testing, and confirmability testing. The conclusion of this study is to determine the concept of dowry in Janjilobi Village, Barumun District, Padang Lawas Regency, and to describe the phenomena that occur in Janjilobi Village, traditional leaders, religious scholars, and several community members. The results of this study indicate that the dowry applied in Janjilobi Village does not violate any laws, either customary or Islamic. There is no prohibition on increasing the dowry, as the dowry rests entirely with the woman.